'I think we've had a health screen': New offshore screening, new refugee health guidelines, new Syrian and Iraqi cohorts: Recommendations, reality, results and review. (9th August 2018) - Heenan, Rachel C; Volkman, Thomas; Stokes, Simon; Tosif, Shidan; Graham, Hamish; Smith, Andrea; Tran, David; Paxton, Georgia
Abstract : Aim: To examine refugee health assessments in Syrian and Iraqi children in the context of changes to offshore immigration screening, updated Australian refugee health guidelines and the primary care refugee health model in Victoria. Methods: This is a retrospective audit of Syrian and Iraqi children aged 0–17 years attending a specialist immigrant health service from January 2015 to September 2017. Results: We saw 128 children (7 months–16 years, 64.8% male). Prior to arrival, 58.9% of children had experienced trauma, and 67.9% had missed at least 1 year of school. Almost all children (93.3%) were linked with a regular general practitioner in Australia, and 23.6% children were linked with a refugee health nurse; offshore health records were infrequently available. Of school‐aged children, 25% were not enrolled in school 3 months after arrival. Only 2 of 113 (1.8%) children had completed a recommended refugee health assessment, and 55.1% had commenced appropriate catch‐up vaccination in primary care. After screening completion, the most prevalent conditions were low vitamin D (63.6%); growth/nutrition (24.2%), neurological/metabolic (16.4%), learning/behaviour (15.6%) and mental health (12.5%) concerns; latent tuberculosis infection (11.8%); and developmental delay (10.2%). Sixteen children required surgery after arrival, and six children had life‐threatening medical conditions on arrival – only one had an offshore critical alert; care for the other five children resulted in 133 unanticipated hospital admission days. Conclusions: There are substantial challenges with the current primary care screening model in Victoria. Disability, developmental and mental health concerns were prominent in this cohort, and many children had delays in education access, compounding prior disadvantage.